2004
DOI: 10.1001/archderm.140.9.1087
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Margins for Lentigo Maligna and Lentigo Maligna Melanoma

Abstract: Objectives: To assess the margins required for excision of lentigo maligna (LM) and lentigo maligna melanoma (LMM) by the technique of mapped serial excision (MSE), and to assess the efficacy of MSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
114
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 32 publications
8
114
1
Order By: Relevance
“…[3][4][5][6][7] Nine studies (including the current study) report clearance rate with 5-mm margins to be only 0% to 86% (Table IV). [3][4][5][6][7][24][25][26] Further, residual melanoma in situ is unlikely to be detected by routine bread-loafing sections of the excised specimen 27 and 8% to 20% will recur. [28][29][30] Certainly, we should strive for better.…”
Section: Recommended Margin For Standard Excisionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] Nine studies (including the current study) report clearance rate with 5-mm margins to be only 0% to 86% (Table IV). [3][4][5][6][7][24][25][26] Further, residual melanoma in situ is unlikely to be detected by routine bread-loafing sections of the excised specimen 27 and 8% to 20% will recur. [28][29][30] Certainly, we should strive for better.…”
Section: Recommended Margin For Standard Excisionmentioning
confidence: 99%
“…Our recurrence rate of 0.3% is consistent with previously published recurrence rates using Mohs micrographic surgery or staged excision (Table IV). [3][4][5][6][7][24][25][26]38,39 If we add the 12 patients who would not have cleared with the recommended 9-mm margin, then up to 15 patients may have recurred. The maximum projected recurrence rate for 9-mm margins is therefore 1.4%.…”
Section: Low Recurrence Validates Recommended Margin and Mohs Microgrmentioning
confidence: 99%
“…[18][19][20][21] Staged excision of melanoma is another alternative excision method that promises not only to retain tissue sparing but also to allow for paraffin-embedded tissue processing, thus avoiding any keratinocyte freeze artifact. [22][23][24][25][26][27][28] In addition, marginal evaluation is performed by a trained dermatopathologist, something that we consider to be extremely important for delineating lesional margins because melanocytic hyperplasia may be difficult to differentiate from melanocytic neoplasia (ie, MIS) even for a trained, experienced dermatologist. Staged excision, to date, has demonstrated low rates of persistence of 0% to 7% among all published data.…”
mentioning
confidence: 99%
“…3,5,8 Numerous studies have demonstrated that margins of 0.5 to 1.0 cm are inadequate for complete excision of LM and LMM, respectively. 5,[8][9][10][11][12][13][14] Because of poorly defined clinical margins, unpredictable subclinical extension, and the head and neck location, margin-controlled surgical techniques such as staged excision with rush paraffin-embedded permanent sections and Mohs micrographic surgery have been proposed for the treatment of LM and LMM with low recurrence rates of 0.5% to 5%. [12][13][14][15][16][17][18] We report our experience with 117 LM and LMM cases excised with a staged technique and rush permanent sections.…”
mentioning
confidence: 99%